A Welcome Proposal to Amend the GMO Legislation of the EU. Issue 11 (November 2018) - Eriksson, Dennis; Harwood, Wendy; Hofvander, Per; Jones, Huw; Rogowsky, Peter; Stöger, Eva; Visser, Richard G.F.
Abstract : Is the European Union (EU) regulatory framework for genetically modified organisms (GMOs) adequate for emerging techniques, such as genome editing? This has been discussed extensively for more than 10 years. A recent proposal from The Netherlands offers a way to break the deadlock. Here, we discuss how the proposal would affect examples from public plant research.